Antifungal and Mechanism of Perilla Essential Oil against Candida tropicalis and Pichia kluyveri - Xiaohong ZHOU; Ting CAI; Zixi LIN; Dafeng ZHANG; Shan ZHANG; Wenliang XIANG (Shipin gongye ke-ji, 2023)
The inhibiting the pellicle formation has always been an important problem that urgently needs to solve the fermented vegetable industry. Perilla essential oil (PEO) has broad-spectrum antimicrobial properties because of its natural bioactive compounds and is widely used in food products. At present study, the main components of PEO were analyzed to explore the antifungal activity of PEO against the film-forming microorganisms Candida tropicalis SH1 and Pichia kluyveri SH2 in fermented vegetables-Sichuan pickle. The antifungal mechanism of PEO was explored by observing cell morphology, cell membrane integrity, intracellular protein leakage and mitochondrial membrane potential changes, and the influence of PEO on the flavor of Sichuan pickle was also measured. The results showed that PEO could not only inhibit the growth of Candida tropicalis and Pichia kluyveri, but also endow fermented vegetables with flavor. The minimum inhibitory concentration (MIC) of PEO against C. tropicalis and Pichia kluyveri were 0.4 μL/mL, and minimum fungicidal concentration (MFC) were 1.6 and 0.8 μL/mL, respectively. After MIC and MFC treatment with PEO, the cell morphology and cell membrane of the strains were changed, the protein concentration increased, and the membrane potential decreased significantly. These results would provide scientific basis and theoretical guidance for the construction and optimization of the preservative method of fermented vegetables.